Decoupling Europe - Gabriel Felbermayr; Steffen Gans; Hendrik Mahlkow; Alexander-Nikolai Sandkamp (Kiel Institute for the World Economy (IfW), 2021)
The COVID-19 pandemic revealed the vulnerability of international value chains in the face of global shocks. This has triggered a political discussion regarding a possible reshoring of vulnerable supply chains back home. The aim is to reduce dependencies on foreign suppliers and thus improve crisis resilience of the domestic economy. The debate is also rooted in the growing dependence on Asian suppliers and the colliding political and ideological systems between China and the West. Unilateral decoupling of the EU from China (a doubling of trade costs) would reduce real income in the EU on average by 0.8 percent. In terms of GDP in 2019, this equals a permanent loss in real income of 131.4 bn EUR. Should China retaliate, real income would fall by 1.0 percent (170.3 bn EUR). With its extremely interconnected economy, real income in Germany would even decline by 1.4 percent (48.4 bn EUR). China would also lose from such a trade war, with real income declining by 1.3 percent. Should the EU increase its trade barriers against all its non-European trading partners, real income in the Union would fall by 3.5 percent or 584.3 bn EUR in case of a unilateral increase and by 5.3 percent or 873.1 bn EUR in case the rest of the world responds by also raising trade barriers. – – Die COVID-19 Pandemie hat die Verletzbarkeit internationaler Wertschöpfungsketten in Folge globaler Schocks offengelegt. In der politischen Diskussion werden seitdem Rufe nach einer Renationalisierung vulnerabler Lieferketten laut, um die Abhängigkeit von ausländischen Zulieferern zu verringern und die heimische Wirtschaft krisenfester zu machen. Hintergrund dieser Debatte ist auch die zunehmende Abhängigkeit von asiatischen Zulieferern verbunden mit zunehmenden politischen und ideologischen Spannungen zwischen China und dem Westen. Eine einseitige Abkopplung der EU von China würde die Wohlfahrt über alle EU-Mitgliedsstaaten im Durchschnitt um 0,8 Prozent reduzieren. Gemessen am BIP 2019 entspräche dies einem dauerhaften Einkommensverlust in Höhe von 131,4 Mrd. EUR. Sollte China zurückschlagen, so würde das Realeinkommen um 1 Prozent sinken (170,3 Mrd. EUR). Aufgrund seiner starken internationalen Verflechtungen wäre Deutschland mit einem Einkommensverlust in Höhe von 1,4 Prozent (48,4 Mrd. EUR) besonders stark betroffen. China würde durch solch einen Handelskrieg Einkommenseinbußen in Höhe von 1,3 Prozent erleiden. Sollte die EU ihre Handelsbarrieren gegenüber allen außereuropäischen Handelspartnern erhöhen, so wäre das Realeinkommen in der Union 3,5 Prozent bzw. 584,3 Mrd. EUR niedriger. Im Falle eines Handelskriegs würde sich dieser Verlust auf 5,3 Prozent bzw. 873,1 Mrd. EUR erhöhen.
Keywords: 330; European Union; China; Germany; Trade; Global Value Chains; Europäische Union; Deutschland; Handel; Globale Wertschöpfungsketten